QuantiFERON-TB Gold Plus for screening and monitoring latent tuberculosis infection in spondyloarthritis patients - Zehra Ozsoy; Adem Ozdemir; Mustafa Ekici; Emre Bilgin; Asena Eken; Zeynep Saribas; Ahmet C Inkaya; Deniz Koksal; Burcin Sener; Ihsan Ertenli; Omer Karadag; Levent Kilic (Journal of Infection in Developing Countries)
Introduction: The optimal frequency of rescreening for latent tuberculosis infection (LTBI) in patients with inflammatory arthritis on biologic/targeted-synthetic disease modifying anti-rheumatic drugs (b/ts-DMARDs) is uncertain. We aimed to evaluate the impact of LTBI re-screening using the QuantiFERON-TB Gold Plus (QFT-Plus; QIAGEN, Germantown, USA) test method and to assess the frequency of re-screening in real-life spondyloarthritis (SpA) patients on b/ts-DMARDs.